Report of Motor Developmental Delay Screening of Infants (4-18 Months Old) of Karaj City - Farin Soleimani; Ehteram Khoshbin; Sedigheh Shams (University of Social Welfare and Rehabilitation Sciences, 2001)
This study has screened 6150 infants between 4-18 months by Infanib Scoring. In this assessment infants divided to three group Normal, Transient and Abnormal by 20 items that based on French angles, Reflexes, Tone and posture. The transient group was visited 1 month later and the abnormal group was referred to pediatric neurologist for diagnostic evaluation and to rehabilitation center for treatment. The Infanib was selected because of high validity and reliability in the previous studies, and in this study the results show that the sensitivity, specificity, positive and negative predictive value is equal to 90%, 81%, 85% and 87%. Thus the Infanib is proposed as an appropriate screening test in the developing countries because of quantified, reliable measurement of body tone and posture, short time for examination, and the ability of occupational and physical therapist, nurses and physician to perform it.